Community Service Program for Enhancing UMKM Competitiveness Through Formalization and Halal Certification - Rachmadio, R. Edy; Syahlan, Fatra; Amir, Miftah; Nugraha, Derry (PT Agung Media Publisher, 2025)
This community service initiative responds to the pressing issues faced by Micro, Small, and Medium Enterprises (MSMEs) in Nagrak Sub-district, Sukabumi Regency, particularly in strengthening business formalization, halal assurance, and global market preparedness through the UMKM Juara (Champion MSMEs) program. Using a participatory action research framework, the program engaged 45 MSME actors representing five key sectors namely food processing, beverages, traditional snacks, handicrafts, and cosmetics. The activities unfolded through four interconnected phases needs assessment, training and public outreach, individualized mentoring, and continuous monitoring and evaluation carried out over a six-month period from May to October 2024. The program recorded substantial, quantifiable progress. A total of 38 MSMEs (84.4%) successfully secured their Business Identification Numbers (NIB) via the Online Single Submission system, marking a decisive transition from informal to formal business practice. In parallel, 32 participants (71.1%) submitted complete halal certification dossiers, and 18 of them had already obtained provisional certificates by the end of the program. Knowledge assessments further showed a significant leap in understanding, with average scores rising from 48.3% to 82.7%, reflecting a 71.2% improvement across all training modules. The food processing sector achieved the highest rate of halal certification submissions at 94.4%, while handicrafts and cosmetics encountered greater obstacles due to more intricate material-tracing processes. The integrated strategy combining regulatory compliance assistance, certification facilitation, and holistic capacity building proved effective in dismantling multiple developmental constraints simultaneously. Nevertheless, sustained advancement toward genuine global competitiveness will require long-term reinforcement, particularly in post-certification market access, international buyer networking, and ongoing product innovation support.